Interventions to Improve Sensory Tactile, Auditory, and Visual Down Syndrome Children by Families - Hiremawati, Anik Dwi; Rochyadi, Endang; Sunardi, Sunardi; Rakhmat, Cece (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Various interventions aimed at addressing sensory challenges are available for Down Syndrome children, but interventions made based on the results of sensory intervention are exciting challenges to research. This study aims to determine the improvement of sensory abilities through stimuli designed based on the results of sensory. This study used a pre-post quantitative method that measured the sensory skills of Down syndrome children. The study was conducted on 8 participants of Down Syndrome children for 12 months. Data analyzed using the Wilcoxon rank test obtained an Asymp value. Sig. (2-tailed) or p-value < 0.05 so that the conclusion is rejected H0 or sufficient evidence that the pretest and post-test sensory development values are different and Asymp values are obtained. The application of examination-based sensory interventions reportedly provided significant improvements in sensory skills in 8 Down Syndrome children after receiving based interventions by following procedures and validated interventions in the form of guidance for parents for 12 months of routine home interventions.